(untitled) (Fiep Bulletin - online, 2014)
the relationship between a sense of satisfaction and chosen components of attitudes towards physical activity and physical education was the main object of this study. 229 students of one of public post-secondary schools in opole was examined for this research, using sWls-test (scale of life satisfaction - adaptation Z. jurczynski 2001) and author survey questionnaire. the study shown a statistically signifi cant correlation between the perceived level of life satisfaction and behavioral component of attitudes towards physical activity and emotional - to quantity of physical education. it is worth to promote physical activity as a way of improving the quality of human life.